Hubungan Tingkat Pengetahuan Pengawas Menelan Obat Dengan Keberhasilan Pengobatan Pasien Tuberkulosis Paru Di Kabupaten Klaten - Joko Tri Atmojo (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Knowledge Level PMO, Success Tuberculosis Treatment. DOTS strategy in Klaten district had begun since 2000 for all community health centers. The success of DOTS in tuberculosis treatment influenced by some factor. One of the factors is PMO behavior to tuberculosis disease. But in 2013, the cure rate in tuberculosis treatment that community health centers have done has decreased. If not cure, it makes an economic and psychological load. The germ in the lung could be resistant and it could infect other people for the same resistant. To determine the relationship between the knowledge level of PMO and the success of tuberculosis treatment. The research was conducted in Klaten district in September – October 2014. The design of this research was a cross-sectional study. Research subjects are PMO that registered in the TB register Health Department District of Klaten in the first quarterly and second quarterly 2013 that can be evaluated in first quarterly and second quarterly 2014 came from 34 community health centers. Total subjects are 97 persons. Data were obtained through questionnaires and direct interviews. Data analysis was held step by step which includes univariate and bivariate analysis using the Kendall tau test. Knowledge level of PMO was significant statistically to the success of tuberculosis treatment (PR = 13,333;95% CI = 3,583 to 49,612 with p-value = 0,004). Knowledge level of PMO that proved to be a risk factor of success tuberculosis treatment